2017
DOI: 10.21162/pakjas/17.3647
|View full text |Cite
|
Sign up to set email alerts
|

CORRELATION OF BIOCHEMICAL LEAF TRAITS AND GALL FORMATION IN SIX CULTIVARS OF MANGO, Mangifera indica L.

Abstract: Mango (Mangifera indica L.) leaves are susceptible to severe attack by insect gall formers. The study's objective was to assess how different vertical strata of the tree canopy and variation in leaf traits affect gall formation. For this, individual and temporal variation in leaf traits of different mango cultivars (Anwar ratole, Chaunsa, Dusehri, Fajri, Sindri and Siroli) and their ultimate effect on gall formation were studied in 2009-10. In addition, the approximate quantity of carbon, nitrogen, phosphorus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In other studies, gall formation was found to be affected by different vertical strata of the tree canopy and variations in leaf traits [ 18 , 19 ]. Gall abundance on Mangifera indica leaves was found to be higher in the upper than the lower zone of the plant canopy, which on its turn was higher than in the inner zone [ 20 ]. In a type of aphidic gall, the number/size of the gall is different when a kind of aphid feeding on the different site of the same host [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, gall formation was found to be affected by different vertical strata of the tree canopy and variations in leaf traits [ 18 , 19 ]. Gall abundance on Mangifera indica leaves was found to be higher in the upper than the lower zone of the plant canopy, which on its turn was higher than in the inner zone [ 20 ]. In a type of aphidic gall, the number/size of the gall is different when a kind of aphid feeding on the different site of the same host [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fusiform and horned galls have certain common traits, such as specific reticulate schizogenous ducts associated with the vascular bundles, that fill the inner wall, and expanded xylem in the stalk that serves as a strong support and facilitates the exchange of nutrients [42]. As mentioned above, some studies have shown that the host plant can affect the anatomy and metabolism of galls [20][21][22][23]. In this study, we tested two galls produced by two galling aphids, and hypothesized that the morphology and developmental pattern differ because of their different stimulation sites.…”
Section: Introductionmentioning
confidence: 99%